Noteworthy Cardiac Literature 2019: Cerebral Protection, Zone 2 Arch, Intravascular Ultrasonography in Dissection, Heart Allocation, and Mitral Durability. (June 2020) - Ghincea, Christian V.; Reece, T. Brett; Aftab, Muhammad; Cleveland, Joseph C.; Pal, Jay D.
The year of 2019 continues to have notable literature advancing the practice of cardiac surgery. In this article, topics of discussion will include the evolution of cerebral protection, the advancement of arch surgical techniques, the heart transplant allocation system, and mitral repair approach and durability.